Development and Validation of a Scale for Christian Character Assessment for Young Children1 - Kim, Sungwon (Religions, 2019)
The emphasis on character education that has emerged from the Nuri national curriculum and the Character Education Act is leading the direction of Korean education. However, the lack of a proper scale of character assessment-especially Christian character for young children-has caused uncertainty in related studies. This study aims to develop and validate a scale that assesses Christian character for young children. The data was collected from 257 (study 1) and 405 (study 2) Christian children who attend church and kindergarten or day care center. Within 12 factors, 67 questions were developed, which were subsequently refined to 39 questions by seven professors. The Christian character scale for young children was finalized to twenty-four questions through exploratory factor analysis and confirmatory factor analysis within four factors: piety, self-control/harmony, responsibility/independence, and caring/respect.